ANTI-MICROBIAL RESISTANCE IN PAKISTAN: A PUBLIC HEALTH ISSUE - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2017)
Anti-microbial or antibiotic resistance is a global public health problem, more dominant in the developing countries. Illiteracy and lack of awareness among the general population is a leading cause, compounded by lack of concern by the physicians and the pharmacists selling drugs over the counter. Another side of the phenomenon is attributed to profit making goals of pharmaceutical companies and weak regulation of the market. Nevertheless, misuse and overuse of antimicrobials accelerates this process. Besides, health issues, anti-microbial resistance also has economic implications on the health care system, where the simpler treatments are becoming difficult, day by day. Enforcement of standard treatment guidelines for the health providers and behavior changes at the patients' end are likely to bring about a change in the situation. Keywords: Antibiotics; Anti-microbial Resistance; Public health; Pakistan